COMPARATIVE STUDY BETWEEN CONVENTIONAL AND CONSERVATION TILLAGE SYSTEM OF CORN CULTIVATION IN NGANJUK REGENCY, EAST JAVA PROVINCE OF INDONESIA - Nina Lisanty; Nugraheni Hadiyanti; Agustia Dwi Pamujiati; Rasyadan Taufiq Probojati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Corn cultivation techniques can be performed using a conventional tillage system (CovTS) and conservation tillage system (CosTS), which consists of minimum tillage (MT) and no-tillage (NT) systems. These systems have been implemented by almost every corn-producing region in Indonesia. One of these areas is Patianrowo District, Nganjuk Regency of East Java Province, Indonesia. The study was conducted to analyze the comparison from the economic side, such as the use and cost of farming inputs, revenue, income, and farming feasibility of the two cultivation systems. The study applied the methods of interview, documentation, and literature study in collecting the required data. Differences in costs, income, and the R/C ratio of maize farming from the two cultivation systems were tested statistically for independent samples. The analysis results stated that the no-tillage system was economically more profitable than the conventional system. A higher R/C Ratio value indicated that the NT system was more efficient in using costs, coupled with production time, than the CovTS. However, statistically, the two cultivation systems did not differ in production and income but showed a significant difference in labor employment. The condition of an area experiencing labor difficulties and supported by soil types such as grumosol is suitable for implementing a no-tillage system. In this case, the local government, through field extension officers, can guide farmers' decision to apply either cultivation system. Providing information, knowledge, and skills will assist maize farmers and other related parties in making decisions to obtain maximum profit and increase welfare.